THE URGENCE OF INVESTIGATION TERMINATION ORDERS (SP2LID) IN THE CRIMINAL ACTION INVESTIGATION PROCESS AS IMPLEMENTATION OF THE CIRCULAR LETTER OF THE KAPOLRI NUMBER : SE/7/VII/2018 - Azan Fujiyanto; Otong Rosadi; Iyah Faniyah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The Circular Letter of the Chief of Police Number: SE/7/VII/2018 concerning the termination of investigations is a rule made to fill a legal vacuum regarding the termination of investigations within the Police. This rule regulates the mechanisms and rules for stopping investigations that have been carried out to answer the community's need for legal certainty for reports that have been made previously. Legal certainty in the investigation process if the report or complaint previously made does not meet the criminal element or there is not enough evidence then the investigation must be stopped, answering the cessation of the investigation is published in the Internal Police Circular Letter Number: SE/7/VII/2018 concerning the termination of the investigation. also occurred within the West Sumatra Regional Police. This research is a descriptive analytical research. The approach used in this study is a normative juridical approach which is supported by an empirical juridical approach. The data used in this study are secondary data and primary data. All data and materials obtained from the research results were compiled and analyzed qualitatively, and presented in a qualitative descriptive form. From the results of the research, it can be explained that the urgency of SP2Lid as the implementation of the issuance of Circular Letter Number: SE/7/VII/2018 in the process of investigating criminal acts is that to fill the legal vacuum regarding the mechanisms and procedures for stopping investigations that are not regulated in the Criminal Procedure Code, as well as being instructions regarding procedures for implementing the requirements in the investigation process addressed to Polri investigators, because the Chief of Police has the authority to issue circulars containing instructions or notifications regarding the provisions for stopping the investigation if in the case of the investigation the facts and evidence collected are not sufficient or the event is not a criminal act, the investigator can stop the investigation and not continue it to the investigation stage but if one day the reporter or investigator gets new facts and evidence (novum) then the previous stage of the investigation will be removed. The arrest can be reopened by going through the case title mechanism and then the investigator issues a Further Investigation Order.Keywords: SP2LID, Investigation, Crime, SE/7/VII/2018.